Game audio development : game development essentials. - Marks, Aaron, ....-; Novak, Jeannie, 1966- (New York : Delmar Cengage Learning, 2009)
Create game audio from the ground up with this comprehensive, multi-faceted resource designed for industry beginners and professionals alike! Game audio makes up one-third of the overall game experience: an experience that is part of the larger, multi-billion dollar video gaming industry. Game Audio Development tackles the complex world of audio by addressing all three major game audio disciplines: music composition, the creation of sound effects, and dialog performances. It begins by providing readers with a solid background and history of the discipline, and then progresses into equipment, techniques, skills, and coordinating these factors to produce effective audio that will enhance the gaming experience. The book concludes with a forecast for the future of game audio.